1975
DOI: 10.1159/000180493
|View full text |Cite
|
Sign up to set email alerts
|

Number of Nephrons in Normal Human Kidneys and Kidneys of Patients with the Congenital Nephrotic Syndrome

Abstract: A method of graded sieving for counting of glomeruli in removed kidneys is described. The number of nephrons (glomeruli) in six normal kidneys deriving from autopsies of three children 22–73 months of age was 1.82 ± 0.35 × 106. The results give a little higher number than most previous studies with which they are compared. In the kidneys of two 10- and 15-month-old patients with the congenital nephrotic syndrome of the Finnish type the mean number of nephrons was 3.17 ± 0.52 × 106 which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 11 publications
4
16
0
Order By: Relevance
“…The number per kidney is 0.88 x 106 in the control kidneys, but as high as 1.53 x 10ft in the CNF kidneys, a difference of 74%. This agrees with the pre vious study in which the sieving method was used, and in which the mean glomerular number in four CNF kidneys was shown to be about 70% higher than in seven control kid neys [6].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The number per kidney is 0.88 x 106 in the control kidneys, but as high as 1.53 x 10ft in the CNF kidneys, a difference of 74%. This agrees with the pre vious study in which the sieving method was used, and in which the mean glomerular number in four CNF kidneys was shown to be about 70% higher than in seven control kid neys [6].…”
Section: Resultssupporting
confidence: 91%
“…The disease is inherited as an autosomal recessive trait [3] with an exceptionally high incidence in Finland, 12.4:100.000 births [4], Histological examination shows glomerular changes like mesangial hypercellularity, scler osis of the capillary tuft and fibrosis, and the proximal tubuli are often ectatically dilated with epithelial cell atrophy [2,5]. Recently, it has been shown that the number of glomeruli is about 70% higher in kidneys from patients with CNF than in normal kidneys, being 3.2* I0'1 and l.8*IO fi, respectively, when using a sieving method for the counting of glomeruli [6],…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glomeruli were isolated from 8-to 12-wk-old adult mice and from human cadaver kidneys that were unsuitable for transplantation (from the IV Department of Surgery of Helsinki, Finland). The isolation methods have been described previously (23,27). The Western blotting was done following standard procedures using polyvinyl difluoride membrane and horseradish peroxidase-conjugated secondary antibody (Amersham Biosciences).…”
Section: Western Blottingmentioning
confidence: 99%
“…The isolation of kidney glomeruli was performed by sieving as described [17]. Isolated glomeruli were homogenized with Ultra-Turrax (Rose Scientific Ltd, Alberta, Canada) in 0.08 M Tris-HCl pH 6.8 buffer containing 2% SDS and 10% glycerol.…”
Section: Western Blottingmentioning
confidence: 99%